2004
DOI: 10.1097/01.ju.0000130510.28768.f5
|View full text |Cite
|
Sign up to set email alerts
|

15-Year Experience With the Management of Extrinsic Ureteral Obstruction With Indwelling Ureteral Stents

Abstract: At almost 1 year followup stent failure due to extrinsic compression occurred in nearly half of treated patients. Analysis of data revealed a diagnosis of cancer, baseline mild renal insufficiency and metastatic disease requiring chemotherapy or radiation as predictors of stent failure. Managing extrinsic compression by retrograde stenting continues to be a practical but guarded decision and should be tailored to each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
4
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 17 publications
4
141
4
6
Order By: Relevance
“…[7][8][9] A failure rate of 43% (20 of 46 stents) for extrinsic ureteral obstruction was first reported by Docimo and Dewolf. 7 Similar failure rates of 42% (58 of 138) 1 and 36% (56 of 157) 9 were reported in 2 larger retrospective series. In a prospective study of stent placement in 92 patients with intrinsic obstruction or malignant external obstruction, the MUO subset had significantly higher rates of failure (44% vs 27%, p ϭ 0.001).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…[7][8][9] A failure rate of 43% (20 of 46 stents) for extrinsic ureteral obstruction was first reported by Docimo and Dewolf. 7 Similar failure rates of 42% (58 of 138) 1 and 36% (56 of 157) 9 were reported in 2 larger retrospective series. In a prospective study of stent placement in 92 patients with intrinsic obstruction or malignant external obstruction, the MUO subset had significantly higher rates of failure (44% vs 27%, p ϭ 0.001).…”
Section: Discussionsupporting
confidence: 81%
“…Because of the novel stent material and design, we hypothesized that risk factors for failure identified for traditional stents, including the presence of malignant bladder invasion, 9 distal level of obstruction 8 and increased serum creatinine, 1,8 would not impact the outcome of this metallic device. Notably Cox regression analysis revealed that patients with prostate cancer invading the bladder at cystoscopy had a significantly increased risk of failure (HR 6.50, 95% CI 1.45-29.20, p ϭ 0.015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,5 The severity of hydronephrosis was graded by ultrasonography according to the grading system of the Society for Fetal Urology (SFU). 6 Performance status (PS) was evaluated according to the Eastern Cooperative Oncology Group (ECOG) PS.…”
Section: Methodsmentioning
confidence: 99%
“…The median survival of patients with MEUO ranges from 3 to 7 months. [1][2][3][4] In such patients with MEUO, retrograde ureteral stenting is usually considered as an initial treatment. However, adequate stent placement across an obstructed ureteral segment does not necessarily guarantee adequate urine drainage.…”
Section: Introductionmentioning
confidence: 99%